Determination of Rifampicin, Isoniazid, and Pyrazinamide Simultaneously in Tablet Formulation Using UV Spectrophotometry Method with Mean Centering of Ratio Spectra - Rida Evalina, Tarigan; Asti Eliani, Siregar; Chemayanti, Surbakti (Asian Journal of Pharmaceutical Research and Development, 2024)
This research aims to simultaneously determine Rifampicin(RI), Isoniazid(IN), andPyrazinamide(PZ) in tablet formulation using the UV spectrophotometry method with Mean Centering Of Ratio Spectra (MCR). The absorption spectra of RI (6-18 μg/mL), IN (5-15 μg/mL), and PZ (6-12 μg/mL) solutions were scanned within the 200-400 nm range. For RI determination, the RI spectra were divided by the IN spectrum at 10 μg/mL, and the resulting ratio spectra were mean-centered. For IN determination, the IN spectra were divided by the PZ spectrum at 9 μg/mL, and the ratio spectra were mean-centered. For PZ determination, the PZ spectra were divided by the RI spectrum at 12 μg/mL, and the ratio spectra were mean-centered.Method validation parameters were assessed, including linearity, accuracy, precision, Limit of Detection (LOD), and Limit of Quantification (LOQ). The linearity values were 0.9997 for RI, 0.9990 for IN, and 0.9994 for PZ. Accuracy was 100.71% for RI, 100,40% for IN, and 100.31% for PZ. Precision was 0.14% for RI, 0.14% for IN, and 0.11% for PZ. The LOD values were 2.66μg/ml for RI, 1.30μg/ml for IN, and 1.40μg/ml for PZ. The LOQ values were 4.85μg/ml for RI, 3.94μg/ml for IN, and 4.24μg/ml for PZ. All parameters met the International Conference on Harmonization (ICH) requirements.The MCR method effectively for the simultaneous determination of RI, IN, and PZ in the tablet formulation.